Struktur Semantis Verba “melaksanakan” dalam Bahasa Jawa Kuno - Sura, Eka; Ratna Erawati, Ni Ketut (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 27 No 1 (2020): MaretDO - 10.24843/ling.2020.v27.i01.p03, 2020)
This research article focuses in analyzing the semantic structure of the verb "doing" in literature work of old javanese languange. The data was collected from Old Javanese Languange literary works such as Adiparwa and lontar Bhuana kosa using the observation method and note-taking techniques. The data were analyzed using distribution method. Distribution method was used to analyze semantic structure by using Natural Semantic Metalanguange (NSM) theory developed by Goddard and Wierzbicka (2014). The results shows that “doing” verb in Old Javanese Languange consists of verbs magawe, makirtya, nangun, makardi, makerti, and mayasa. Each verb had distinctive features that differentiate one verb to the others.